Effects of missed anti-tuberculosis therapy doses on treatment outcome: a multi-center cohort studyResearch in context - Isabella B.B. Ferreira; Rodrigo C. Menezes; Mariana Araújo-Pereira; Valeria C. Rolla; Afrânio L. Kritski; Marcelo Cordeiro-Santos; Timothy R. Sterling; Cody Staats; Gustavo Amorim; Anete Trajman; Bruno B. Andrade; A. Benjamin; et al. (The Lancet Regional Health. Americas, 2025)
Summary: Background: Tuberculosis (TB) remains a leading cause of infectious disease mortality globally. Although directly observed therapy (DOT) has been widely implemented to improve adherence, nonadherence continues to compromise treatment success rates, especially in real-world settings. Therefore, this study aims to assess the impact of missed doses on TB treatment outcomes. Methods: Prospective study that followed adults with drug-sensitive TB for two years after TB treatment initiation at five clinical centers of the RePORT-Brazil cohort between June 2015 and June 2019. Participants not in DOT or followed for less than 30 days were excluded. Nonadherence was defined as the percentage of missed doses relative to the prescribed regimen, monitored daily through DOT. The primary composite outcome comprised treatment failure, disease recurrence, drug resistance, death, or loss to follow-up (LTFU) after 30 days of treatment. Associations were assessed with multivariable logistic regression. Findings: Among the 578 participants analyzed, 218 (37·7%) experienced unfavorable outcomes. Overall, 23% of participants missed more than 10% of prescribed doses, and this group had an 81·2% likelihood of experiencing unfavorable outcomes, compared to only 21·6% among those with complete adherence. A significant association was observed between the percentage of missed doses and unfavorable outcomes (adjusted OR: 1·11, 95% CI: 1·07–1·14, p-value < 0·0001). Interpretation: Even minor nonadherence in TB treatment was associated with an increased risk of unfavorable outcomes, highlighting the role of adherence in successful TB care. Funding: Fundação Oswaldo Cruz, Fundação José Silveira, Departamento de Ciência e Tecnologia, US National Institute of Allergy and Infectious Diseases.